Efficacy of cabazitaxel in fourth or later line of therapy in metastatic castration-resistant prostate cancer: multi-institutional real-world experience in Germany : clinical bladder cancer - Wenzel, Mike; Borkowetz, Angelika; Lieb, Verena; Hoffmann, Manuela A.; Borgmann, Hendrik; Höfner, Thomas; Dotzauer, Robert; Neuberger, Manuel; Worst, Thomas; Hardenberg, Jost von; Linxweiler, Johannes; Klümper, Niklas (Urologic oncology, 2022)
Objective: Since multiple oncological treatment options in metastatic castration-resistant prostate cancer (mCRPC) are available, optimal sequencing of therapies are under investigation. However, the efficacy of Cabazitaxel (CAB) in fourth and later lines of therapy is rarely investigated. Material and Methods: Fifty three patients with mCRPC treated with CAB in fourth line or later were included in our retrospective study, which involved eight uro-oncology centers in Germany. Clinical and tumor characteristics, as well as PSA-response rates were analyzed. Kaplan-Meier plots addressed overall survival (OS) and progression-free survival (PFS). Logistic regression models predicted risk factors of overall mortality (OM). - Results - Of 53 patients, 79% (n=42), 19% (n=10) and 2% (n=1) received CAB in fourth, fifth and sixth line. A median of 4 cycles of CAB were administered. Median PSA at start of CAB was 199ng/ml (interquartile range (IQR) 70-869). In total, 89% had bone and 40% visceral metastases prior to the start of CAB. Moreover, 30% of patients received Docetaxel in first line therapy for mCRPC. Most frequent sequence of therapy was abiraterone followed by docetaxel and followed by enzalutamide. Overall, median PSA-response rate was -20% (IQR -80 to +10%). Patients with docetaxel in first line had a significantly better median PSA-response on CAB (-80 vs. 20%, P=0.03). Median OS, radiographic PFS and overall PFS were 14.8 (Confidence interval (CI): 11.0-20.8), 3.0 (CI: 2.9-4.0) and 2.9 (CI: 2.0-3.3) months, respectively. In multivariable analyses, visceral metastases, PSA >100ng/ml, ISUP4+5 and later administration of Docetaxel were predictors of OM. Conclusion: Real-world experiences indicate that favorable oncologic outcomes can be achieved with CAB especially regarding PSA-response and OS even in the fourth line or later in patients with mCRPC.
Online verfügbar: 14 October 2022, Artikelversion: 14 November 2022
Gesehen am 27.06.2023